2007
DOI: 10.1007/s12247-007-9012-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Calibration for Efficient Method Development: Analysis of Tablet API Concentration by Near-Infrared Spectroscopy

Abstract: Near-infrared (NIR) spectroscopy is an important process analytical technology (PAT) tool for rapid characterization of pharmaceutical tablet quality. The time and expense required for calibration development has been a detriment to implementation of PAT sensors. While methods based on generalized least-squares and net analyte signal pure-component projection (PCP) have been demonstrated to be useful tools for efficient spectroscopic calibration, PCP methods are relatively difficult to deploy and maintain in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…5A). These results offer a better understanding of the spectral relationship with tablet hardness presented in literature 10–12. This also illustrates why tablets with thickness of less than 4 mm can have a significant spectral scaling when produced with a thickness SD as low as 0.1 mm, which can add to prediction errors and outlier potential (Figs.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…5A). These results offer a better understanding of the spectral relationship with tablet hardness presented in literature 10–12. This also illustrates why tablets with thickness of less than 4 mm can have a significant spectral scaling when produced with a thickness SD as low as 0.1 mm, which can add to prediction errors and outlier potential (Figs.…”
Section: Resultssupporting
confidence: 57%
“…Numerous studies in literature examined the use of NIRS to predict tablet density and hardness. Many of the published papers describe baseline shifts in reflection mode in correlation with sample densities 10, 11. Research from Ciurczak and Drennen12 on predicting tablet hardness using NIR suggested that the increased absorption in harder tablets is probably due to a reduction of light scattering on the smoother surface of these harder tablets, allowing more light to penetrate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to efficient calibration, synthetic spectra can also be used for risk assessment. The use of synthetic calibration has already been demonstrated in agricultural, pharmaceutical and biomedical applications [2,10,11]. Although the addition of interference signals to pure component spectra in synthetic calibration is essentially analogous to the interference projection and shrinking in NAS and GLS, respectively, a rigorous side-by-side theoretical and practical comparison of these techniques has not been published.…”
Section: Efficient Calibration and Synthetic Calibrationmentioning
confidence: 99%
“…Regarding the randomly generated concentration values, the blending composition of Design 7 (0.15/0.283/0.567, w/w) was used as the mean values for individual components. The relative standard deviation for all three components was set to be 25%; as reported that relative standard deviation larger than 10% did not present significant difference on the calibration performance [10]. In addition, the blending composition of Design 7 was also used as the weight factor (w 2 ) for individual components.…”
Section: Synthetic Calibration Datasetmentioning
confidence: 99%
“…[32] The technique is a valid PAT tool for the rapid characterization of pharmaceutical tablet quality. [33] ICH Q8 (R1) guidelines have mentioned the possible use of NIR spectroscopy for real time release testing of tablets such as weight variation. [34] The guideline described the method to be superior to compendia end-product testing.…”
Section: Process Analytical Technology and Tablet Evaluation By Nirmentioning
confidence: 99%